Au NPs decorated holey g-C3N4 as a dual-mode sensing platform of SERS and SALDI-MS for selective discrimination of L-cysteine - Pei, Jingxuan; Sun, Yibo; Yu, Xiang; Tian, Zhenfei; Zhang, Shuting; Wei, Songbo; Zhao, Yanfang; Boukherroub, Rabah (Journal of colloid and interface science, 2022)
[Display omitted] •Au@hg-C3N4 hybrids were fabricated as a dual-mode matrix of SERS and SALDI-MS.•The holey structure enhances matrix enrichment and prevents Au NPs agglomeration.•Au@hg-C3N4 matrix exhibits high sensitivity and superior reproducibility for l-cys.•The matrix reliably detects l-cys and distinguishes its enantiomers in human serum. Development of reliable sensing strategy combining surface-enhanced Raman scattering (SERS) and surface-assisted laser desorption/ionization-mass spectrometry (SALDI-MS) is of significant interest to distinguish cysteine enantiomers in body fluid for understanding their physiological roles and toxicity hazards. In this work, a SERS/SALDI-MS dual-mode sensing platform of gold nanoparticles (Au NPs) decorated holey carbon nitride (hg-C3N4) was fabricated for sensitive detecting cysteine. The designed Au@hg-C3N4 matrix featured a uniform distribution of Au NPs with the help of anchoring effect of hg-C3N4 holey structure, which was conducive to produce highly repeatable signals. Moreover, the combination of Au NPs and holey g-C3N4 endowed this matrix with superior enrichment capacity, enhanced charge transfer and strong UV absorption. These merits allowed the matrix to acquire high sensitivity and enhanced reproducibility for l-cysteine by means of SERS/SALDI-MS. Likewise, reliable detection of l-cysteine and efficient recognition of d-cysteine in human serum jointly revealed its prospect for detecting cysteine enantiomers in body fluids. This work offers a reliable SERS/SALDI-MS strategy for determining L/D-cysteine enantiomers, and the designed Au@hg-C3N4 matrix becomes a potential application candidate for selective detection of bio-enantiomers.